Research Progress with Atractylone as an Antitumor Agent - Ying Yao; Guanghuan Shen; Jianghan Luo; Jinhong Wang; Zheng Xu; Hao Wang; Linlin Cui (Molecules)
Atractylone is a sesquiterpenoid compound extracted from Rhizoma Atractylodis. As one of the main active components in the volatile oil of the Atractylodes genus, it has exhibited certain therapeutic effects, including anti-inflammatory, antiviral, antioxidant, antiallergic, antiangiogenic, and neuroprotective activities, among others. With further research on the chemical constituents and pharmacology of sesquiterpenes, research on the antitumor activity of Atractylone has also been further expanded. Much of the current literature pays particular attention to the antitumor activity of Atractylone, which was found to inhibit the apoptosis of tumor cells and prevent growth, invasion, and migration through different apoptosis pathways and signaling pathways. Due to its promising potential for cancer prevention, it may play a role in reducing the incidence of malignant tumors. In this paper, the antitumor activity and mechanism of Atractylone are reviewed, providing a reference to inform future research on the tumor treatment, clinical application, and further development and utilization of this plant genus.